Removal of arsenate by electrocoagulation reactor using aluminum ball anode electrodes - Goren, A. Y.; Oncel, M. S.; Demirbas, E.; Sik, E.; Kobya, M. (Iwa Publishing, 2018)
The aim of this research was to remove arsenate (As(V)) from groundwater using an air-injected electrocoagulation (EC) reactor with aluminum (Al) ball anodes. The effects of seven operating variables - initial pH, applied current (i), operating time (t(EC)), initial As(V) concentration (C-o), Al ball anode diameter (d(p)), reactor column height (h), and airflow rate (Q(air)) were investigated with a Box-Behnken statistical experimental design. ANOVA results from the quadratic model equations indicated that the model fitted very well with the experimental data for the responses, which were removal efficiency, operating cost (OC), As(V) adsorption capacity, and effluent concentration (R-2 >= 0.87). The most effective parameters were applied current, operating time, and anode height for As(V) removal efficiency in the EC reactor, while initial pH, Al anode diameter, and air flow rate had limited effect on removal. The model predicted a residual As(V) concentration below 10 mu g/L under the optimum operating conditions (pH 7.03, 0.29 A, 10.5 min, d(p) 7.5 mm, 613.4 mu g/L, h 5.1 cm, and Q(air) 6.4 L/min). The maximum As(V) removal efficiency and minimum OC in the EC process were almost 99% and 0.442 $/m(3), respectively.
Keywords: Al ball anodes; arsenate removal; Box-Behnken design; electrocoagulation